Los nombres, ?con o sin artículo? - Montero Gálvez, Sonia (Vestnik za tuje jezike, 2014)
The present work is a didactical proposal designed to be implemented in the classroom at an initial or elementary level of Spanish as a Second Language. This proposal aims to introduce the use and meaning of three types of noun phrases: a) the bare nouns (plurals and mass nouns) as referential expressions of unspecified amounts; b) the noun phrases introduced by the indefinite article (un/una/unos/unas) as referential expressions of single units, and c) the noun phrases introduced by the definite article (el/la/los/las) as generic or individuative references. This proposal is based on a cognitive approach to the extent that not only it's nourished by the contributions of Cognitive Grammar regarding nominal expressions in English, but it attempts to offer a cognitive vision of the issues in Spanish, highlighting an essential meaning for each type of noun phrases. Furthermore, it's supported by a contrastive approach in order to identify the most relevant aspects on which an introduction to the mentioned grammatical issues should be focused. The proposed approaches and suggestions are in line with those proposed in a doctoral thesis that is currently in progress. Therefore, we should take into account that both this didactical proposal as well as the doctoral thesis on which it is based are not legitimised yet by the academic and scientific community. However, we are venturing to share this work because it may be helpful in the teaching and learning of Spanish as a Second Language.
Keywords: Spanish; španščina; tuji jeziki; samostalniki; določni členi; nedoločni členi; poučevanje jezikov